Oxidative Stress and Cognitive Decline: The Neuroprotective Role of Natural Antioxidants - Franzoni, Ferdinando; Scarfò, Giorgia; Guidotti, Sara; Fusi, Jonathan; Asomov, Muzaffar; Pruneti, Carlo (Frontiers in Neuroscience, 2021)
Free- radicals (Oxygen and Nitrogen species) are formed in mitochondria during the oxidative phosphorylation. Their high reactivity, due to not-engaged electrons, leads to an increase of the oxidative stress. This condition affects above all the brain, that usually needs a large oxygen amount and in which there is the major possibility to accumulate "Reacting Species". Antioxidant molecules are fundamental in limiting free-radical damage, in particular in the central nervous system: the oxidative stress, in fact, seems to worsen the course of neurodegenerative diseases. The aim of this review is to sum up natural antioxidant molecules with the greatest neuroprotective properties against free radical genesis, understanding their relationship with the Central Nervous System.